2018
DOI: 10.1101/391490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Single Adaptive Mutation in Sodium Taurocholate Cotransporting Polypeptide Induced by Hepadnaviruses Determines Virus Species-specificity

Abstract: 24Hepatitis B virus (HBV) and its hepadnavirus relatives infect a wide range of vertebrates from 25 fish to human. Hepadnaviruses and their hosts have a long history of acquiring adaptive mutations. 26However, there are no reports providing direct molecular evidence for such a coevolutionary "arms 27 race" between hepadnaviruses and their hosts. Here, we present evidence suggesting the adaptive 28 evolution of the sodium taurocholate cotransporting polypeptide (NTCP), an HBV receptor, has been 29 influenced by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…At approximately week 48 or 96, of the presence or absence abnormal NTCP does not play an important role any longer. Second, HBV may evolve sophisticated means to evade or directly counteract the entry restriction factor NTCP and replication inhibitor NAs as a consequence of the continuous interaction with wild-type or mutant NTCP and NAs ( Kluge et al, 2015 ; Jacquet et al, 2019 ; Takeuchi et al, 2019 ). Using phylogenetic analyses, Jacquet et al, (2019) even found that NTCP has been under recurrent positive selection during primate evolution, suggesting that one hallmark of pathogenic virus-host relationships is the reciprocal evolution of host receptors and viral envelope proteins as a result of their antagonistic interaction over time.…”
Section: Discussionmentioning
confidence: 99%
“…At approximately week 48 or 96, of the presence or absence abnormal NTCP does not play an important role any longer. Second, HBV may evolve sophisticated means to evade or directly counteract the entry restriction factor NTCP and replication inhibitor NAs as a consequence of the continuous interaction with wild-type or mutant NTCP and NAs ( Kluge et al, 2015 ; Jacquet et al, 2019 ; Takeuchi et al, 2019 ). Using phylogenetic analyses, Jacquet et al, (2019) even found that NTCP has been under recurrent positive selection during primate evolution, suggesting that one hallmark of pathogenic virus-host relationships is the reciprocal evolution of host receptors and viral envelope proteins as a result of their antagonistic interaction over time.…”
Section: Discussionmentioning
confidence: 99%